Sebaran Tingkat Kematangan Gonad (TKG) Ikan Layang (Decapterus russelli) di Perairan Pasongsongan, Kabupaten Sumenep - Wilda Maskuriyah; Muhammad Zainuri (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
Indian Scad, Decapterus russelli is the catch that dominates the Pasongsongan Fishing Port. The Indian Scad are caught throughout the year using the purse seine with and FADs. The intensity of catching,the number of vessels which tend to continue to increase in number, and the used of FADs can put greater pressure on the sustainability of the fish resources. Therefore, information on biological aspects, namely knowing the distribution of Gonad Maturity Level (Tingkat Kematangan Gonad/TKG) and Fecundity of Indian Scad in Pasongsongan waters is used as the objective of this research. This research was conducted in November 2019 - November 2020. The data analysis carried out was the Gonad Maturity Level (TKG) and its distribution based on the length and weight of the fish and their fecundity. The results showed that the distribution of the gonad maturity level varied from TKG I to TKG V for each month. However, based on the season, all levels of TKG can be seen from the catch both in the dry and rainy season. The fecundity of the fish in the dry season ranges from 5,929 - 25,470 points while in the rainy season it ranges from 364 - 23,216.